Formulasi dan uji aktivitas antibakteri sediaan gel antiseptik tangan ekstrak daun puring (Codiaeum variegatum) - Repining Tiyas Sawiji; Elisabeth Oriana Jawa La (Health Sciences and Pharmacy Journal, 2022)
The high incidence of infection occurs due to a lack of public awareness in getting used to a clean and healthy life. Hands are one of the media for the spread of bacteria, so an antibacterial preparation is needed. Puring leaf (Codiaeum variegatum) is a plant that contains many components of secondary metabolites, one of which is tannin compounds. Based on previous research, it has been proven that the tannin group has antibacterial activity. The use of puring leaves directly on the hands is considered less practical so it needs to be formulated in the form of hand antiseptic gel preparations. This study aims to design a hand antiseptic gel formula with variations in the concentration of puring leaf extract and to determine the antibacterial activity of hand antiseptic gel preparations from puring leaf extract against Staphylococcus aureus bacteria. This type of research was experimental laboratory. Puring leaves were first extracted using 96% ethanol as solvent and three hand antiseptic gel formulations were made with varying concentrations of extract, namely FI (1.5%), FII (4.5%), and FIII (6%) with a base gel using carbopol 940. The physical tests included organoleptic and homogeneity tests, pH tests, dispersion tests, and viscosity tests. The data obtained were analyzed using ANOVA and Kruskal Wallis. The antibacterial activity test was measured using the paper disk diffusion method. The results showed that the three formulations of hand antiseptic gel preparations puring leaf extract met the physical characteristics of good gel preparations and FIII had the highest antibacterial activity against Staphylococcus aureus with an inhibitory diameter of 3.16±0.28. Antibacterial activity in hand antiseptic gel preparation of puring leaf extract is in the weak category. Keywords: Antibacterial; puring leaf; paper disk difusi; antiseptic gel